Especies y distribución geográfica de los subgéneros de Simulium (Diptera: Simuliidae) en Costa Rica - Vargas V, Mario (Universidad de Costa Rica, 1997)
Ninety eight streams, 50 located in the Central Valley and 48 in the Atlantic and Pacific lowlands of Costa Rica, were surveyed monthly during the first year and binlonthly the second year (July 1968-June 1970). The specimens (larvae and pupae) were preserved in 85% alcohol and mature pupae were placed in a humid chamber to obtain the adults. Immature blackflies were collected. subgenera of Simulium (Díptera: Simulüdae). In the following, those marked with asterisk are first records for Costa Rica. S. panamense was the most common species, followed by S. metallicum, S. sambont. S. pseudocallidum*. S. puigi*, S. lewisiAutzianum*,S. travisi,  S. callidum. S. ochraceum*, S. gonzalezt. S. quadrivittatum and S. clark.i*. In 88 of these streams, at least one species of Simulium were found. in 29, one species. in 33 two species, in 17 three species, in 5, four species, in 3, five species and in one, six species. There is a wide distribution of S. metallicum (38 streams) and S. ochraceum was found in five streams: both species ¡;:re considered the main vectors of Onchocerca volvulus in Central America. and S. callidu"" S. pseudocallidum and S. quadrivittatum as secondary vectors of such filarla.